Carolina built : a novel - Alexander, Kianna (Gallery Books, 2022)
"Josephine N. Leary is determined to build a life of her own, and a future for her family. When she moves to Edenton, North Carolina from the plantation where she was born, she is free, newly married, and ready to follow her dreams. As the demands of life pull Josephine's attention-deepening her marriage, mothering her daughters, supporting her grandmother-she struggles to balance her real estate aspirations with the realities of keeping life going every day. She teaches herself to be a business woman, to manage her finances, and to make smart investments in the local real estate market. But with each passing year, it grows more difficult to focus on building her legacy from the ground up. Moving and inspiring, Josephine Leary's untold story speaks to the part of us that dares to dream bigger, tear down whatever stands in our way, and build something better for the loved ones we leave behind"--